Catchment hydrological response and transport are affected differently by precipitation intensity and antecedent wetness - J. L. A. Knapp; J. L. A. Knapp; W. R. Berghuijs; W. R. Berghuijs; M. G. Floriancic; M. G. Floriancic; J. W. Kirchner; J. W. Kirchner (Hydrology and Earth System Sciences)
Hydrological response and travel times characterise distinct catchment behaviours that have both been intensively studied but rarely together. The hydrologic response characterises how quickly, and how strongly, streamflow reacts to precipitation inputs, whereas transport characterises how quickly precipitation travels through the system to reach the stream. Here we use sub-daily time series of hydrometeorological fluxes and stable water isotopes to quantify both hydrological response and transport in two intensively studied temperate catchments. Consistent with previous studies, we find that hydrologic response is much quicker than transport. However, we also find that catchment wetness and precipitation intensity influence hydrologic response and transport in different ways. Increased antecedent wetness results in stronger runoff responses, primarily by mobilising more old water, while increased precipitation intensity results in faster propagation of the runoff response signal and delivery of greater proportions of recent precipitation to streamflow. Considered together, response times and travel times provide insights into runoff generation mechanisms, flow paths, and water sources.